Some Results on Reduced Rings - Baghdad Science Journal (مجلة بغداد للعلوم)
The main purpose of this paper is to study some results concerning reduced ring with another concepts as semiprime ring ,prime ring,essential ideal ,derivations and homomorphism ,we give some results a bout that.